Correlates of ultrasound diagnosed non alcoholic fatty liver disease in Indian adults with features of metabolic syndrome - Imran Nazir Salroo; Musharaf Bashir; Rayees Ahmad Bhat; Sheikh Imran Sayeed (National Scientific Medical Center, 2020)
Because of its complex pathogenesis and scarcity of approved therapies, non-alcoholic fatty liver disease is considered as one of the major challenge before mankind. Literature suggests that non-alcoholic fatty liver disease will replace Hepatitis C as a major form of chronic liver disease in adults and children over the next decade thus becoming the major cause of liver transplantation. Aim: To assess anthropometric, biochemical parameters and correlates of ultrasound-diagnosed non-alcoholic fatty liver disease patients. Material and methods: For this study a total of 182 subjects were selected from the department of Radiodiagnosis and Imaging, SKIMS medical college, Bemina, Srinagar, Jammu and Kashmir, India. Control group consisted of 91 age and sex matched subjects (mean age 51.69 ± 13.97 years) whereas case group consisted of 91 subjects (mean age 50.72 ± 12.13 years). Ultrasound under standardized conditions was performed in all subjects and the grading of non-alcoholic fatty liver disease was done in case group. Correlation of anthropometric and biochemical parameters with the non-alcoholic fatty liver disease was sought from the case group. Results: Non-alcoholic fatty liver disease patients had significantly higher body mass index [BMI (p<0.0001***)] and waist-to-hip ratio (p<0.003**), fasting glucose levels (p<0.0001***) and triglycerides (p<0.0001***). Furthermore, a positive correlation between the waist (inches) and non-alcoholic fatty liver disease was found. Conclusion: Our findings further support that patients with signs of metabolic syndrome are at increased risk to develop non-alcoholic fatty liver disease. Furthermore abdominal obesity is an independent risk factor for non-alcoholic fatty liver disease.